Analisa Kualitas Briket Arang dari Cangkang Kelapa Sawit Dengan Rasio Perekat Amylum dan Ukuran Partikel Terhadap Parameter Produk Briket - nuna, jama; putra, kaha (LENVARI, 2024)
One solution to reduce kerosene consumption is by utilizing waste from palm kernel processing to create biochar briquettes. These biochar briquettes are made from palm kernel shells and serve as a dense alternative energy source. Additionally, biomass charcoal can also be used as an alternative fuel. Biomass charcoal has a high calorific value and produces minimal smoke and emissions when burned. Various biomass materials, including palm kernel shells, wood, and coconut husks, can be used. The study aims to determine the burnable surface area of briquettes within a specific time frame. Particle size and adhesive percentage affect the charcoal density on the briquette surface, which, in turn, influences combustion speed. The results indicate that the burnable surface area of the samples is quite small. Furthermore, the study measures the ignition time required for briquettes to burn completely. On average, the samples burn for 90 to 114 minutes. Although there is no significant difference in burn time between mesh sizes 40, 50, and 60, the reference sample burns for up to 3.5 hours.